Analysis of electrical energy harvesting from piezoelectric integrated shallow conical composite shells in metastable configurations using mixed formulation - Aimmanee, Sontipee; Phongsitthisak, Chanasit (Composite structures, 2022)
This article presents a study of energy harvesting from smart composite Belleville springs, which are truncated conical shallow shells bonded with piezoelectric patches. When the springs subject to mechanical loading–unloading cycles, electrical energy is generated from the integrated piezoelectric elements via the direct piezoelectric effect. A mixed strong and weak form mathematical model composed of strain energy and electric enthalpy is formulated to analyze the electro-elastic performance of the shells. Undergoing snap-through and snap-back buckling when loaded and unloaded in compression, the smart Belleville springs in metastable configurations exhibit unprecedented complex electromechanical behaviors, which can be applied to enhance energy scavenging. The developed model is firstly validated with the finite-element method using ABAQUS™ and the responses from both approaches are in excellent agreement. Parametric studies on the spring geometry are systematically conducted to determine geometrical effects on stored electrical energy in the piezoelectric patches. The numerical results obtained from the mixed-form model show that snap buckling in the metastable conical shells can be used to harvest a relatively large amount of electrical energy. Conclusions of this study lay down a design guideline for energy extraction from the smart composite Belleville springs with a variety of geometric and kinematic constraints.